Pan‐cancer analyses reveal genomics and clinical characteristics of the melatonergic regulators in cancer. Issue 3 (5th September 2021) - Zhang, Jian; Jiang, Huali; Du, Kunpeng; Xie, Tao; Wang, Baiyao; Chen, Chengcong; Reiter, Russel J.; Cen, Bohong; Yuan, Yawei
Abstract: Melatonin, an endogenous hormone, plays protective roles in cancer. In addition to regulating circadian rhythms, sleep, and neuroendocrine activity, melatonin functions in various survival pathways. However, the mechanisms of melatonin regulation in cancer remain unknown. In the present study, we performed a comprehensive characterization of melatonin regulators in 9125 tumor samples across 33 cancer types using multi‐omic data from The Cancer Genome Atlas and Cancer Cell Line Encyclopedia. In the genomic landscape, we identified the heterozygous amplification of AANAT and GPR50, and heterozygous deletion of PER3, CYP2C19, and MTNR1A as the dominant alteration events. Expression analysis revealed methylation‐mediated downregulation of melatonergic regulator expression. In addition, we found that melatonergic regulator expression could be used to predict patient survival in various cancers. In depth, microRNA (miRNA) analysis revealed an miRNA‐mRNA interaction network, and the deregulated miRNAs were involved in melatonin secretion and metabolism by targeting circadian clock genes. Pathway analysis showed that melatonergic regulators were associated with inhibition of apoptosis, the cell cycle, the DNA damage response, and activation of RAS/MAPK and RTK signaling pathways. Importantly, by mining the Genomics of Drug Sensitivity in Cancer database, we discovered a number of potential drugs that might target melatonergic regulators. In summary, this study revealed the genomic alteration and clinical characteristics of melatonergic regulators across 33 cancers, which might clarify the relationship between melatonin and tumorigenesis. Our findings also might provide a novel approach for the clinical treatment of cancers.